Firm-Value Effects of Carbon Emissions and Carbon Disclosures—Evidence from Korea - Jeong-Hwan Lee (MDPI AG, 2021)
We examine the association between carbon emissions, carbon disclosures, and firm value for Korean firms, with a particular interest in chaebols, a special type of Korean conglomerate. Using hand-collected carbon emissions and firm-specific data for 841 Korean firms, including 514 chaebols and 335 non-chaebols, we find a significantly positive relationship between carbon emissions and firm value among chaebol affiliates. This result contrasts with previous findings conducted in advanced markets, where investors consider carbon emissions to be destructive. In terms of the voluntary disclosure policy, we find that companies with good environmental performance tend to disclose carbon emissions voluntarily. We further argue that these findings originate from the specific business atmosphere in Korea. Our results support the traditional view of corporations in terms of environmental policy and highlight the importance of firm characteristics and historical developments in the analysis of environmental policy.